2012
DOI: 10.1002/j.1532-2149.2012.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

CC‐chemokine ligand 4/macrophage inflammatory protein‐1β participates in the induction of neuropathic pain after peripheral nerve injury

Abstract: Background: Neuropathic pain is caused by neural damage or dysfunction and neuropathic pain-related symptoms are resistant to conventional analgesics. Neuroinflammation due to the cytokine-chemokine network may play a pivotal role in neuropathic pain. We demonstrate that macrophage inflammatory protein-1b (MIP-1b) participates in neuropathic pain. Methods: Mice received partial sciatic nerve ligation (PSL), and tactile allodynia and thermal hyperalgesia were assessed by von Frey test and Hargreaves test, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 37 publications
(48 reference statements)
3
61
0
1
Order By: Relevance
“…The up-regulation of these chemokine ligands (e.g., central CCL2 and CCL3, peripheral CCL4) has been separately shown in rodents with chronic pain [25, 4042]. The present study is the first to document that these three chemokine systems are simultaneously up-regulated in diabetic primates and that neuroinflammation appears to be permanent in primates with chronic disease.…”
Section: Discussionsupporting
confidence: 56%
“…The up-regulation of these chemokine ligands (e.g., central CCL2 and CCL3, peripheral CCL4) has been separately shown in rodents with chronic pain [25, 4042]. The present study is the first to document that these three chemokine systems are simultaneously up-regulated in diabetic primates and that neuroinflammation appears to be permanent in primates with chronic disease.…”
Section: Discussionsupporting
confidence: 56%
“…Among the CCR5 ligands, CCL3 and CCL4 appear to be important in neuropathic pain development. Using neutralizing antibodies, Saika et al (2012) showed that CCL3 contributes to the progress of thermal hyperalgesia and tactile allodynia, unlike CCL4, which contributes mainly to tactile allodynia. In 2010, the upregulation of CCL3 in macrophages and Schwann cells in a murine partial sciatic nerve ligation model and the parallel the development of pain was documented (Kiguchi et al, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…When a nerve is injured, histamine, inflammatory cytokines, and chemokines are released from mast cells located in the damaged nerve, inducing the activation and accumulation of neutrophils and macrophages to the nerve site. Subsequently, inflammatory cytokines and chemokines released from the accumulated cells sensitize the primary sensory nerves, 1,2) increasing the release of pain transmitters from the primary sensory nerve endings, resulting in an unusual enhancement of the effect of the pain transmitters on secondary sensory nerves. 3,4) The effect of pain transmitters on secondary sensory nerves is further augmented by the activation of microglia, [5][6][7][8][9] a type of glia cell, in the spinal cord.…”
mentioning
confidence: 99%